The Musical-Drama Television Film “Bung Karno Under The Breadfruit Tree” - I Komang Arba Wirawan (Institut Seni Indonesia Denpasar, 2022)
The purpose of this research is to create a Musical-Drama Television Film titled “Bung Karno di Bawah Pohon Sukun” (Bung Karno Under the Breadfruit Tree), a television film that was initiated to form real learning spaces in the film industry for university students; refresh the creativity of the program in the world of industry (DUDI) in Bali TV; and create a work that provides learning related to the values of nationalism. This product is made of five episodes of 24 minutes each. In short, this film tells the story of Bung Karno's contemplation period when he was exiled in Ende, Flores. After the script preparation, the script breakdown was carried out with workshops, pre-production, and production. The workshop stage was carried out for the maturation of the script material and strengthening the appreciation of the characters. The resource persons presented are as follows: I Gusti Putu Bawa Samar Gantang, Jean Couteau, Warih Wisatsana, Heny Shanti, Happy Salma, and Ida Bagus Purwa Susila. All stages of production have been carried out, namely pre-production, production, post-production and distribution stages. The pre-production stage carried out was the preparation of the script, script breakdown, survey of shooting locations at Nusa Penida, Bangli, and Singaraja, wardrobe, logistics, transportation, accommodation, equipment check, casting, reading, recce, and Pre Production Meeting (PPM) which was attended by the entire division. The second stage is the production that took place in Singaraja, followed by the post-production stage of editing and music scoring. The theory used to dissect this film is the theory of mise en scene (Roland Barthes) to describe the visual aspects of the frame. The research method is descriptive qualitative analysis of the constituent elements and structures of the Musical-Drama Television Film